Kirkon, kruunun ja yhteisön intresseissä – Itsemurha 1600-luvun Ruotsissa - Kanerva Kirsi (Suomalaisen kuolemantutkimuksen seura ry., 2022)
A review of Riikka Miettinen (2015), Suicide in Seventeenth-Century Sweden: The Crime and Legal Praxis in the Lower Court (University of Tampere, School of Social Sciences and Humanities. 576 pp.)